Principles of environmental and resource economics : a guide for students and decision-makers - Folmer, Henk; Gabel, H. Landis (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar, 2000)
"This thoroughly revised and updated edition of a classic text provides a comprehensive, non-technical overview of the principles of environmental and resource economics. The distinguished group of authors offers both an introduction to the economic causes and consequences of environmental and resource problems and an assessment of recent developments in environmental policy instruments and corporate responses to environmental problems." "Comprehensive and authoritative, this edition of Principles of Environmental and Resource Economics offers a non-technical state-of-the-art review which will be widely used as a teaching tool for upper undergraduate students and above as well as a reference point for practitioners and researchers."--Jacket.
Includes bibliographical references and index.
rpm 19/09/2016
Loans
Keywords: Environmental economics; Natural resources; Natural resources -- Management; Economics